POTENTIAL ASSESSMENT OF GREENHOUSE GAS REDUCTION IN PATTAYA HOTELS, THAILAND - Suwanphitak, Tawika; Fukuda, Suneerat; Chaiwiwatworakul, Pipat (MATTER: International Journal of Science and Technology, 2021)
Hotels in Thailand are one of the country’s main economic growth sectors which inevitably result in increased sector energy use and cause a rise in GHG emissions. A study on the source of GHG emissions in the hotel sector can guide the suitable reduction measures. This paper reports the study results of the greenhouse gas (GHG) emissions and their reduction potential in 4- and 5-star hotels in Pattaya, Thailand. In the study, seven 4- and 5-star hotels participated in surveys to assess their GHG emissions from electricity use, stationary combustion, mobile combustion, refrigerant leak, wastewater, solid waste, and outsourced laundry. The data used in this study were based on the 2018 statistics. The average emission by the surveyed hotels was at 4,466.99 tCO2e/year, equivalent to 107.88 kgCO2e/m2-year, and 45.42 kgCO2e/room-night. Electricity use was the major activity accounting for 77% of the total emissions. Hence, the GHG reduction plan was put forth to the energy efficiency improvement of energy-intensive machines. The findings from surveyed hotels were used as the basis to estimate the GHG emissions and potential reduction for 4- and 5-star hotels in the whole of Pattaya. By the proposed improvement scheme, the potential to reduce the GHG emission was 13,818.28 tCO2e, for an equivalent reduction of 7.8% of the total GHG emissions. This study approach for GHG reduction can further be applied to other tourism hotels nationwide to support the country in achieving the national GHG emission reduction target and the sustainable tourism industry.